An economic mechanism for request routing and resource allocation in hybrid CDN–P2P networks. (11th May 2015) - Garmehi, Mehran; Analoui, Morteza; Pathan, Mukaddim; Buyya, Rajkumar
Summary: Hybrid content delivery networks (HCDN) benefit from the complementary advantages of P2P (Peer to Peer) networks and CDNs (Content Delivery Network). In order to extend a traditional CDN and enable it to offer hybrid content delivery service, we have modified a traditional domain name system‐based request routing mechanism. The proposed scheme relies on an oligopolistic mechanism to balance the load on the edge servers and employs a truthful profit‐maximizing auction to maximize the contribution of users in the P2P content delivery. In particular, economics of content delivery in HCDNs is studied, and it is shown that through our request routing mechanism, it is possible to deliver higher quality of service to majority of end‐users, increase the net profit of the HCDN provider and decrease the content distribution cost at the same time. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The proposed request routing mechanism delivers high QoS to majority of end‐users, increases the net profit of the hybrid content delivery network–peer‐to‐peer provider and decreases the content distribution cost at the same time.